The Interpersonal Exchange Model of Sexual Satisfaction: Implications for Sex Therapy with Couples - Byers, E. Sandra (Canadian Journal of Counselling and Psychotherapy, 2007)
Although much has been written about the treatment of sexual dysfunction and sexual dissatisfaction, the enhancement of sexual satisfaction has received little attention in either the empirical or clinical literature. Most of the literature on sexual satisfaction that does exist has lacked a definition of the construct. In addition, until recently, there has not been a theoretical model to guide either research or our understanding of factors influencing sexual satisfaction. In order to fill these gaps, Lawrance and Byers (1995) developed and established the validity of the Interpersonal Exchange Model of Sexual Satisfaction (IEMSS). This article first discusses issues related to defining sexual satisfaction and proposes a definition of the construct. Second, the exchange perspective in general and the IEMSS in particular are described. Third, the results of studies which have validated the IEMSS with Canadians in long-term relationships, Canadians in dating relationships, and married individuals living in China are presented. Finally, the implications of the IEMSS for clinical practice are elaborated.